Infrared ion spectroscopy in a modified quadrupole ion trap mass spectrometer at the FELIX free electron laser laboratory - Martens, Jonathan; Berden, Giel; Gebhardt, Christoph R.; Oomens, Jos (Review of scientific instruments, 2016)
We report on modifications made to a Paul-type quadrupole ion trap mass spectrometer and discuss its application in infrared ion spectroscopy experiments. Main modifications involve optical access to the trapped ions and hardware and software coupling to a variety of infrared laser sources at the FELIX infrared free electron laser laboratory. In comparison to previously described infrared ion spectroscopy experiments at the FELIX laboratory, we find significant improvements in efficiency and sensitivity. Effects of the trapping conditions of the ions on the IR multiple photon dissociation spectra are explored. Enhanced photo-dissociation is found at lower pressures in the ion trap. Spectra obtained under reduced pressure conditions are found to more closely mimic those obtained in the high-vacuum conditions of an Fourier transform ion cyclotron resonance mass spectrometer. A gas-mixing system is described enabling the controlled addition of a secondary gas into helium buffer gas flowing into the trap and allows for ion/molecule reactions in the trap. The electron transfer dissociation (ETD) option of the mass spectrometer allows for IR structure characterization of ETD-generated peptide dissociation products.